An integrative review of analytical techniques used in food authentication: a detailed description for milk and dairy products - Ferreira, Mariana Martins (2024)
In the last three decades, the research in food science and food authentication has increased due to numerous discoveries about nutritional needs, toxicities of food components, and the risks associated with improper nutrition and food adulteration. All research results followed the implementation of specific laws about the food components, evaluation of authenticity, and geographic origin. This way, the use of suitable analytical techniques for the identification and quantification of food components, as well as the detection of adulteration, falsification, deliberate substitution, and mislabeling of foods, have great importance in the industrial, scientific, and legislative context. This work is an integrative review of analytical techniques used in food authentication, indicating advantages and disadvantages as well as perspectives for direct, quick, and simple applications, guaranteeing the application of quality standards and ensuring food safety for consumers. Furthermore, this work shows that most previous papers published report the analysis of natural foods to evaluate the origin (traceability) and industrialized foods to detect adulterations and fraud. A focus on research to detect adulteration in milk and dairy products is presented due to the importance of these products in the nutrition of the world population. The main advances and the analytical approaches for the employ of modern analytical techniques in the identification and quantification of milk and dairy products adulterations were discussed, indicating trends and perspectives on food authentication.